Evaluation Of Passenger And Vehicle Transport Systems On KMP. Tarusi And KMP. Lohoraung North Sulawesi Province - Purboyo Purboyo; Irwan Irwan; Muhamad Adief Abdiatama (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Likupang crossing port is one of the ports in North Minahasa regency which has 3 (three) Ro-Ro crossing ships, namely KMP. Lohoraung, KMP. Tarusi, KMP. Watunapato which serves the interisland track in North Sulawesi. In the transportation system security and safety are very important as a form of good service delivery. As well as the arrangement and handling of passenger and vehicle loads on board. However, vehicle loading is above KMP. Lohoraung and KMP. Tarusi not in accordance with established standards. The method used to analyze the existing problems is a qualitative method of manifest analysis of passengers and vehicles, the analysis of the procedures for transporting vehicles on board, the analysis of binding obligations of vehicles on board. While in the existing conditions of the procedures for transporting vehicles on board the KMP.Lohoraung and KMP.Tarusi still not in accordance with the loading of vehicles that have been arranged in PM No.115 of 2016, the obligation of fastening the vehicle on board on the KMP.Lohoraung and KMP.Tarusi is still not in accordance with the obligation to bind the vehicle on board which has been regulated in PM No.30 of 2016, due to the absence of vehicle fastening on board. In order to create security, comfort and safety, things that can be done is to check the appropriate passenger and vehicle manifest form and observe the process of filling in passenger and vehicle data, and implement procedures for transporting vehicles on board.